Etanercept or Methotrexate Withdrawal in Rheumatoid Arthritis Patients in Sustained Remission. Issue 5 (24th March 2021) - Curtis, Jeffrey R.; Emery, Paul; Karis, Elaine; Haraoui, Boulos; Bykerk, Vivian; Yen, Priscilla K.; Kricorian, Greg; Chung, James B.
Abstract : Objective: Patients with rheumatoid arthritis (RA) in whom remission is achieved following combination therapy with methotrexate plus etanercept face an ongoing medication burden. This study was undertaken to investigate whether sustained remission achieved on combination therapy can be maintained with either methotrexate or etanercept monotherapy, as assessed following discontinuation of one or the other medication from the combination. Methods: Of the 371 adult patients with RA who received combination therapy with methotrexate plus etanercept, remission (defined as a Simplified Disease Activity Index [SDAI] score of ≤3.3) was sustained in 253 patients through a 24‐week open‐label period. These 253 patients then entered a 48‐week, double‐blind period and were randomized to receive either 1) methotrexate monotherapy (n = 101), 2) etanercept monotherapy (n = 101), or 3) methotrexate plus etanercept combination therapy (n = 51). Patients who subsequently experienced disease‐worsening received rescue therapy with the combination regimen at the same dosages as used in the initial run‐in period. The primary end point was the proportion of patients in whom SDAI‐defined remission was maintained without disease‐worsening at week 48 in the etanercept monotherapy group as compared to the methotrexate monotherapy group. Secondary end points included time to disease‐worsening, and the proportion of patients in whom SDAI‐defined remission was recaptured after initiation of rescue therapy. Results: Baseline demographic and clinical characteristics of the RA patients were similar across the treatment groups. At week 48, SDAI‐defined remission was maintained in significantly more patients in the etanercept monotherapy group than in the methotrexate monotherapy group (49.5% versus 28.7%; P = 0.004). Moreover, as a secondary end point, sustained SDAI‐defined remission was achieved in significantly more patients who received combination therapy than in those who received methotrexate monotherapy (52.9% versus 28.7%; P = 0.006). Time to disease‐worsening was shorter in those who received methotrexate monotherapy than in those who received etanercept monotherapy or those who received combination therapy (each P < 0.001 versus methotrexate monotherapy). Among the patients who received rescue therapy, SDAI‐defined remission was recaptured in 70–80% in each treatment group. No new safety signals were reported. Conclusion: The efficacy of etanercept monotherapy was superior to that of methotrexate monotherapy and similar to that of combination therapy in maintaining remission in patients with RA. SDAI‐defined remission was recaptured in most of the patients who were given rescue therapy. These data could inform decision‐making when withdrawal of therapy is being considered to reduce treatment burden in patients with well‐controlled RA.